Study on methods to decrease the stress at slaughter in farmed sea bass (Dicentrarchus labrax) - B.M. Poli; G. Mosconi; F. Iurzan; M. Mecatti; F. Scappini; G. Zampacavallo (Italian Journal of Animal Science, 2011)
Fish slaughtering without any avoidable stress is an ethic requirement at consumer and producer level, that also influence product quality. Slaughter methods for marine fish and their impact on fish stress reaction, evolution of post mortem biochemical processes and quality of the final product have been object of few investigations...